Land use pattern of Varanasi city and its environ - Dhanraj Gownamani (National Geographical Journal of India, 2022)
Land is the most important and basic resource for both survival and prosperity of human beings. The utilization of piece of land for the economic benefits is defined as Land use/ Land utilization. Their appraisal, evaluation and efficient utilization are very crucial based on the technological developments, population characteristics of that particular region. Pressure of Population on urban land use is remarkable and needs a thorough analytical evaluation for the proper urban land use planning and its management. This present paper highlights the pattern of land use in Varanasi city. For the purpose of discussion the categories of land use had been broadly divided into Residential, Commercial, Administrative and Tourism land uses. Historical aspects of the cultural landscapes of the sacred city had been discussed elaborately. The city’s multi-lingual, multi-religious, multi-racial and multi-cultural characteristics of population plays a significant role to modify the urban landscape to a considerable extent is highly remarkable.